2017
DOI: 10.3928/1081597x-20170222-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Clinical Outcomes of SMILE and Wavefront-Guided LASIK in Low and Moderate Myopia

Abstract: SMILE and WFG LASIK are efficacious and safe procedures for the correction of low and moderate myopia, but WFG LASIK allows a more predictable outcome and better aberrometric control. [J Refract Surg. 2017;33(5):298-304.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…It has been reported that wavefront-guided LASIK proved the superiority of postoperative CS in comparison to other types of custom ablation [19,20]., and standard LASIK [21,22]. A previous study reported that the CS after wavefront-guided LASIK using the iDESIGN® Refractive Studio was sharper than that produced by small incision lenticule extraction (SMILE) [23,24]. In this present study, wavefrontguided LASIK using a high-resolution aberrometer induced smaller spherical aberration in the 4mm and 6mm pupils.…”
Section: Discussionsupporting
confidence: 46%
“…It has been reported that wavefront-guided LASIK proved the superiority of postoperative CS in comparison to other types of custom ablation [19,20]., and standard LASIK [21,22]. A previous study reported that the CS after wavefront-guided LASIK using the iDESIGN® Refractive Studio was sharper than that produced by small incision lenticule extraction (SMILE) [23,24]. In this present study, wavefrontguided LASIK using a high-resolution aberrometer induced smaller spherical aberration in the 4mm and 6mm pupils.…”
Section: Discussionsupporting
confidence: 46%
“…Some surgeons prefer Laser-in-situ-Keratomileusis (LASIK) over ASA in moderate and even in low myopia as reported by Khalifa et al 19 They prospectively evaluated SMILE and wavefront-guided LASIK for −6 D or less of myopia and found results favoring wavefront-guided LASIK. However, this is beyond the scope of this article.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our findings showed that SMILE induced astigmatism in a small subset of our cohort with preoperative cylinder greater than 0.26 D. Although we don’t believe this was the case in our study, a possible and often cited complication of SMILE is an inadvertent lenticule remnant from incidental tearing that can induce irregular astigmatism [ 35 , 36 ]. Other than this complication, there was limited prior literature addressing any induction of astigmatism with SMILE; however, past publications have consistently shown SMILE inferior to LASIK with regards to astigmatic corrections [ 8 , 37 – 39 ]. There are quite a few reasons why SMILE has a tendency to produce these suboptimal outcomes.…”
Section: Discussionmentioning
confidence: 99%